Pengembangan Bentuk Kebaya Bangaw dengan Sumber Ide Legenda Batoe Tinagat pada Perancangan Adibusana - Anakirin, Nurin Fauhan; Santoso, Ratna Endah (Universitas Negeri Surabaya, 2024)
Foreign cultures that enter Indonesia are slowly eroding the existence of local culture. There is an urgency to preserve and introduce the Tidung Tribe to the community, by developing this traditional kebaya bangaw traditional clothing into a more modern and relevant form to attract the interest of the community today. This design applies the transforming tradition method with 7 stages, namely ATUMICS, with Artefact which is the design object and six basic elements, namely Technique, Utility, Material, Icon, Concept, and Shape to create product innovations or systems that are traditional products so that they can be accepted by modern society while maintaining the cultural values in it. This design produced 9 evening fashion designs, but from the 9 designs, 4 designs were selected to be realized. Based on this design, it can be concluded that the traditional clothing of the Bangaw kebaya can be developed into the design of the costume while maintaining its uniqueness and the source of the idea of the legend of Batoe Tinagat can be used as a source of inspiration in designing the motif of the costume to create an exploration of the more modern traditional clothing of the Tidung tribe through the stages of visual processing, construction, and surface processing.